The Role of Sufism in Moral Development of Students - Ilham Ilahiyah; Yayat Suharyat (International Journal of Global Sustainable Research, 2023)
Education in a broad sense can be interpreted as learning for students (humans), the aim of which is to educate and mature these students. The aim of this research is to gain an in-depth understanding of the role of Sufism in the moral development of school children. This research uses library search. The results of this research discussion show that Sufism is not only a way to bring people closer to Allah SWT, but Sufism in the world of education also makes people have pious character and good and noble behavior. This research concludes that the role of Sufism in the moral development of school children is considered very necessary. The Sufism education model emphasizes the role of ihsan in action which then leads to good behavior.